Development of ionizing radiation mapping robot - Abdul Hafiz bin Zakaria (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Radiation mapping can be used to give information regarding the intensity of radiation at a particular location. Mapping of radiation autonomously using robot as agent will help to prevent harm to human especially when radiation related disaster occur. In this project radiation mapping system consisting of autonomous mobile robot that is equipped with Geiger Muller sensor was developed. A 3D ionizing radiation map is built from the data of the encoder sensor which indicate the location of the mobile robot as well as the radiation data by the Geiger Muller sensor. A grid based algorithm was develop to build the radiation map. The system was tested under several conditions using Cobalt-60 ionizing radiation sources at Malaysia Nuclear Agency indoor radiation facilities. The results shows that the system manage to produce consistent mapping results for repeating experiments with a maximum standard deviation value of 0.9369 µSv/h. This project also evaluated the performance of the Atmel Atmega328 microcontroller under exposure of ionizing radiation Cobalt-60 source. Geant4 software is used to simulate the passage of radiation beams through the Atmel Atmega328 microcontroller model and calculated the estimated absorbed dose rate using Monte Carlo Methods. Microprocessor that is in operation also was tested under the actual ionizing radiation from Cobalt-60 source of with a radiation activity of 0.09 mCi, 0.45 mCi and 2.31 mCi at a distance starting at 20cm and increasing by 20cm until 100cm from the Cobalt-60 source. The test result show that the microcontroller work flawlessly when operating close to source under radiation absorbed dose rate of 28.257 µGy/h. Keywords: Radiation mapping, Autonomous mobile robot, Atmel Atmega328, Geant4,